TERRITORY OF THE CATHOLIC PARISH OF OUR LADY OF THE HELPLESS, ARCHDIOCESE OF TOLUCA, MEXICO - Garduño Rayón, Yabel David (2025)
Catholic parish as a community of the faithful has always been inherently territorial. A delimited territory of a parish is established by the ecclesial authorities and has had distinct functions throughout history. A current process of disengagement of the religious life of the parish community with its territorial delimitation forces to reanalyze their relationships, in cities where mobilization and digital culture originate new territorial processes. The objective of this study was to identify the territory of the parish of Our Lady of the Forsaken, according to its definition, and to clarify it with respect to the territorial delimitation assigned to it. We conducted experiential fieldwork with the parish faithful and the sacred spaces that they appropriated through their religious practices were mapped. The findings contribute to the understanding of the appropriation of Catholic groups in different hierarchies of ecclesial groups and the spatio-temporal dynamicity of their territories.